2021
DOI: 10.1038/s41393-021-00685-7
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the spinal cord injury exercise guidelines in the hospital and community settings: Protocol for a type II hybrid trial

Abstract: Study design Type II hybrid effectiveness-implementation trial protocol. Objectives To (1) evaluate the implementation of coordinated physical activity (PA) coaching delivered by physiotherapists and spinal cord injury (SCI) peers during the transition from in-hospital care to living in a community (implementation objective) and (2) assess the effect of coaching on PA behaviour and psychosocial predictors among people with SCI (effectiveness objective). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A single-group withinsubjects, repeated measures design was used. Details of the study design have been previously reported (14). The implementation evaluation is discussed here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single-group withinsubjects, repeated measures design was used. Details of the study design have been previously reported (14). The implementation evaluation is discussed here.…”
Section: Methodsmentioning
confidence: 99%
“…Four follow-up training/community of practice sessions were completed over the course of 2 years. See Ma et al (14) for further details.…”
Section: Implementation Interventionmentioning
confidence: 99%
“…Limited high-quality trials have focused on the long-term rehabilitation outcomes (e.g., physically active lifestyle, chronic pain, and psychological well-being) of people with SCI living in the community [ 20 , 21 ]. One reason for the lack of trials might be due to barriers of transportation and lack of face-to-face interaction with healthcare professionals [ 22 ]. Two pilot trials that integrated community-based physical activities and telephone counseling from physiotherapists indicated positive effects of an activity-based intervention on functional improvement and physical fitness for community dwellers with SCI [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…PA counseling support services are provided in a variety of settings (e.g. rehabilitation centers or hospitals [ 7 , 8 ], community organizations [ 9 ], fitness centers/gyms [ 9 ], SCI peer mentorship programs [ 10 ], research studies [ 11 ]) and delivered by counselors with different backgrounds and expertise (e.g. SCI peer mentors, physiotherapists, recreation therapists, coaches) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%